The fate of 13C-labelled and non-labelled inulin predisposed to large bowel fermentation in rats. Issue 4 (18th January 2016) - Butts, Christine A.; Paturi, Gunaranjan; Tavendale, Michael H.; Hedderley, Duncan; Stoklosinski, Halina M.; Herath, Thanuja D.; Rosendale, Douglas; Roy, Nicole C.; Monro, John A.; Ansell, Juliet
Abstract : The fate of stable-isotope 13 C labelled and non-labelled inulin catabolism by the gut microbiota was assessed in a healthy rat model. Abstract : The fate of stable-isotope 13 C labelled and non-labelled inulin catabolism by the gut microbiota was assessed in a healthy rat model. Sprague–Dawley male rats were randomly assigned to diets containing either cellulose or inulin, and were fed these diets for 3 days. On day (d) 4, rats allocated to the inulin diet received 13 C-labelled inulin. The rats were then fed the respective non-labelled diets (cellulose or inulin) until sampling (d4, d5, d6, d7, d10 and d11). Post feeding of 13 C-labelled substrate, breath analysis showed that 13 C-inulin cleared from the host within a period of 36 hours. Faecal 13 C demonstrated the clearance of inulin from gut with a 13 C excess reaching maximum at 24 hours (d5) and then declining gradually. There were greater variations in caecal organic acid concentrations from d4 to d6, with higher concentrations of acetic, butyric and propionic acids observed in the rats fed inulin compared to those fed cellulose. Inulin influenced caecal microbial glycosidase activity, increased colon crypt depth, and decreased the faecal output and polysaccharide content compared to the cellulose diet. In summary, the presence of inulin in the diet positively influenced large bowel microbial fermentation.